Simulation of Nb3Al crystalline phase images using multi-slice technique - Wen, Meimei. (2013)
As a promising material in both aerospace and super conducting field, ternary niobium aluminide (Nb3Al) has presented itself with high specific strength at high temperature and capability of operating in strong magnetic field. Its crystal structure is worth exploring, helping understand the root reason that lead to such properties. Transmission Electron Microscope (TEM) is one of the most advanced instruments that can look into material in angstrom scale. However, sometimes it’s better to know roughly what should be expected from the TEM image before the actual operation. Image simulation is such a solution that enables users to simulate high resolution TEM image (HTTEM) of a specimen. By going through the entire procedure of image simulation, one can have a comprehensive understanding of the principles and theories to form such image, the major factors that can affect the quality of an image and the possible causes of errors, getting some intuitive to improve the quality when operating the apparatus. When the incident electron beam of high kinetic energy interacts with the specimen, it’s the atomic potential of the specimen atoms that deviates their wave function. Then the wave function undergoes further phase change when it passes through the objective lens. The image obtained is the reflection of interference of transmitted beam and diffracted beam, or contrast. The task of image simulation is to calculate the wave function at each step, and finally the intensity at the image plane. Multi-slice is a common method used in calculation. This method involves the slicing of a thin specimen and some assumptions to simplify the model, saving calculation time for computer. Fourier transform is the algorithm used in computer and has its advantages and limitations. Lens aberration is inevitable during the image formation. In this project, some of the parameters were discussed in order to obtain an optimized image, such as defocus, spherical aberration, and aperture size. Meanwhile, the thickness and incident energy were also taken into consideration. Nb3Al has a lattice parameter of 5.186 Å, and the atom distance is even smaller than that. The highest point resolution that can be achieved is critical to view distinguished atom spots. Contrast transfer function is used as a reference to calculate the point resolution and show how the above mentioned factors can affect it. By cross reference the final image with crystal structure of the material, it can be concluded that the multi-slice method is useful and handy in image simulation. It provides a comprehensive image in a relatively short period of time.